2023
DOI: 10.1002/cam4.5844
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of esophageal cancer immune prognostic index in advanced esophageal squamous cell carcinoma patients with anti‐programmed cell death‐1 therapy

Abstract: Background: This study aimed to determine whether the immune prognostic index (ECIPI), based on hemoglobin (Hb) and neutrophil-to-lymphocyte ratio (NLR), could predict the prognosis in patients with advanced esophageal squamous cell carcinoma (ESCC) receiving programmed cell death-1 (PD-1) inhibitor treatment. Methods: Advanced ESCC patients who had been treated with PD-1 inhibitors from Jan 2016 to Oct 2021 were included. Kaplan-Meier method and Cox proportional hazards regression were used to analyze progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…Other types of factors include dietary, 10 lymph node metastasis, 11,12 treatment patterns, 13 and molecular biomarkers. 14,15 In recent years,radiomics has been explored to characterize image textures in medical imaging, but there have been limited studies on esophageal cancer. Iwashita et al 16 analyzed skeletal muscle (SM) radiomics and suggested that integrating SM radiomics and clinical data could help determine survival outcomes in patients with esophageal cancer treated with radical radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Other types of factors include dietary, 10 lymph node metastasis, 11,12 treatment patterns, 13 and molecular biomarkers. 14,15 In recent years,radiomics has been explored to characterize image textures in medical imaging, but there have been limited studies on esophageal cancer. Iwashita et al 16 analyzed skeletal muscle (SM) radiomics and suggested that integrating SM radiomics and clinical data could help determine survival outcomes in patients with esophageal cancer treated with radical radiotherapy.…”
Section: Introductionmentioning
confidence: 99%